Effect of Hydrate on Gas/Water Relative Permeability of Hydrate-Bearing Sediments: Pore-Scale Microsimulation by the Lattice Boltzmann Method - Xin Xin (Hindawi-Wiley, 2021)
As a clean energy source with ample reserves, natural gas hydrate is studied extensively. However, the existing hydrate production from hydrate deposits faces many challenges, especially the uncertain mechanism of complex multiphase seepage in the sediments. The relative permeability of hydrate-bearing sediments is key to evaluating gas and water production. To study such permeability, a set of pore-scale microsimulations were carried out using the Lattice Boltzmann Method. To account for the differences between hydrate saturation and hydrate pore habit, we performed a gas-water multiphase flow simulation that combines the fluids’ fundamental properties (density ratio, viscosity ratio, and wettability). Results show that the Lattice Boltzmann Method simulation is valid compared to the pore network simulation and analysis models. In gas and water multiphase flow systems, the viscous coupling effect permits water molecules to block gas flow severely due to viscosity differences. In hydrate-bearing sediments, as hydrate saturation increases, the water saturation Sw between the continuous and discontinuous gas phase decreases from 0.45 to 0.30 while hydrate saturation increases from 0.2 to 0.6. Besides, the residual water and gas increased, and the capillary pressure increased. Moreover, the seepage of gas and water became more tedious, resulting in decreased relative permeability. Compared with different hydrate pore habits, pore-filling thins the pores, restricting the gas flow than the grain-coating. However, hydrate pore habit barely affects water relative permeability.